EFFECTS OF CALCIUM DEPLETION ON THE JUNCTIONAL COMPLEX BETWEEN OXYNTIC CELLS OF GASTRIC GLANDS - Sedar, Albert W. (The Rockefeller University Press, 1964)
In order to ascertain the role of calcium in maintaining the structure of the junctional complex between oxyntic cells, control gastric mucosae of the frog Rana pipiens were compared with those exposed to 1 to 4 mM ethylenediaminetetraacetic acid (EDTA). Changes in transmucosal potential difference and mucosal conductance were monitored. In one case a piece of EDTA-treated mucosa was washed and placed in a Ca(++)-containing solution. Material from all three categories was prepared for electron microscopy (glutaraldehyde and OsO(4) fixation with Epon 812 embedding). Electron micrographs showed that after Ca(++) depletion the intercellular electron-opaque material of the desmosome disappears and the walls of this component separate. Similar changes were observed in the zonula adhaerens. Consistent changes were difficult to detect in the zonula occludens although in some instances disorganization or separation within the tight junction was seen. These effects on the components of the junctional complex were reversible on readministration of Ca(++). The results indicate that Ca(++) is important in maintaining the integrity of the junctional complex. A model correlating the fine structural changes with physiological data is presented.